Gothic bodies : the politics of pain in romantic fiction - Bruhm, Steven (University of Pennsylvania Press, 1994)
An intriguing scholarly investigation, not so much of the ways the late eighteenth and early nineteenth centuries articulated pain, but of the ways in which pain itself articulated the late eighteenth-century experience. Through analysis of novels, plays, and poems, the author explores the transition from sensibility as a sense of "selflessness" to Romanticism, which puts the self in the foreground as the mediating consciousness. His tightly focused discussion sets a starting point for further critical investigation of the subject